Epic [videorecording (Blu-Ray + DVD)] - Wedge, Chris, 1958-; Forte, Lori; Davis, Jerry; Hart, James V.; Joyce, William, 1957-; Hutcherson, Josh; Seyfried, Amanda; Waltz, Christoph, 1956-; Beyoncé, 1981-; Farrell, Colin, 1976-; Ansari, Aziz, 1983- (Twentieth Century Fox Home Entertainment, 2020)
The story of an ongoing battle deep in the forest between the forces of good and the forces of evil. When a teen age girl finds herself magically transported into this secret universe, she must band together with a rag-tag team of fun and whimsical characters in order to save their world, and also ours.